Multi-stakeholder work integrated learning model for higher education - a transdisciplinary approach - Wait, M; Govender, C M (South African Journal of Higher Education, 2016)
Work integrated learning (WIL) is essential to successful higher education curricula and qualifications. Traditional WIL models are discipline specific with collaboration between educator and business aimed at providing the student with workplace experience. There is a need for a transdisciplinary approach to WIL as well as a need to consider multiple stakeholder responsibility in WIL models. This conceptual paper provides a critical review of two discipline specific WIL models in order to reshape them into a third transdisciplinary multi-stakeholder WIL model highlighting the roles of student, education, business and government. Two working WIL models currently in use in two different disciplines, namely the Human Resources and Marketing Departments, were reviewed for similarities and gaps. The review resulted in the proposed Multi-Stakeholder WIL Model. The message of this paper is that for WIL models to be effective and economically viable, government and the students must become key stakeholders.